Mode of Action of Farnesol, the “Noble Unknown” in Particular in Ca2+ Homeostasis, and Its Juvenile Hormone-Esters in Evolutionary Retrospect - De Loof, Arnold; Schoofs, Liliane (Frontiers in Neuroscience, 2019)
Farnesol, the sesquiterpenoid precursor of insect juvenile hormones (JH) that itself has JH activity, existed already long before animals and their hormones came into being. Although it is omnipresent in all eukaryotes, this molecule remains a “noble unknown” in cell physiology. It is neither documented as a hormone nor as another type of signalling molecule. To date, its function as an intermediate in the synthesis of squalene-cholesterol-steroids in chordates/vertebrates, and of the insect/arthropod JHs, esters of farnesol, in the mevalonate biosynthetic pathway is assumed to be the only one. This assumption neglects that already two decades ago, farnesol has been shown to be a potent endogenous inhibitor of N-type voltage-gated Ca2+ channels in some mammalian cell types. The tandem mevalonate pathway and Ca2+ channels originated early in eukaryotic evolution, and has since been well conserved, "promoting" it as a ubiquitous player in control of Ca2+ homeostasis in all eukaryotes. This paper accentuates how this drastic change in thinking gained momentum after the discovery by Paroulek and Sláma that the huge amounts of JH I in male accessory glands of the Cecropia moth, are actually synthesized in these glands themselves and not in the corpora allata, the hitherto assumed unique synthesis site of such compounds. In addition, MAG-JHs have no hormonal- but an exocrine function. Here we hypothesize that MAG-JHs may function in protecting the spermatozoa against toxic Ca2+ concentrations, and in enabling their flagellum to undulate. Our novel paradigm emphasizes the role of the non-genomic membrane receptors that involves the Ca2+-homeostasis system. It classifies Met/Tai and Gce, to date generally thought to be the (only) functional (nuclear) receptors for JHs, as probable Ca2+-sensitive transcription factors. It also assigns to farnesol/JHs a function of hydrophobic molecular valves for restricting untimely Ca2+-passage through some types of canonical Ca2+-channels, and through prenylated-, this means with a covalently farnesyl- or geranyl-geranyl group attached, GPCRs-G proteins as well. In this context, their high flexibility as indicated by a high rotatable bond count, and their horseshoe-shape acquire significance. Some theoretical and practical considerations for possible applications in a medical context will be discussed.